Pulmonary arterial development during childhood: branching pattern and structure. Issue 2 (March 1973) - Hislop, Alison; Reid, Lynne
Abstract : In lungs from 18 children aged between birth and 11 years the development of the branching pattern and structure of the pulmonary arteries, particularly the intralobular and intra-acinar, has been quantitatively analysed after injection with a radio-opaque medium. Up to 18 months of age as new alveolar ducts appear conventional arterial branches develop within the acinus: supernumerary arteries increase in number up to 8 years as new alveoli form. Both types increase in size with age. After birth there is an immediate drop in wall thickness of the vessels below 200 μm diameter while the larger vessels take up to 4 months to fall to adult thickness, suggesting two types of response—one dilatation, the other a growth rate change of the muscle cells. During childhood muscle cell formation in the intra-acinar arteries lags behind increase in artery size so that during childhood few muscular arteries are found within the acinus. The functional significance of these changes is discussed.